The influence of fitness programme for selected motor abilities of junior team hockey players during the preparaton period - Palov, R. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2013)
The present contribution records and evaluates training load by deliberate fitness program of junior team HC 05 in the season 2013/2014 in 9 week mesocycle. The aim of contribution is to verify the effects of deliberate fitness program for the selected motor skills by comparing the recorded values of input and output general motor tests. By evaluating tests, we concluded that our implemented fitness program had an effect on selected motor skills. In all tests we observed an improvement and statistically significant dependence.